2010
DOI: 10.1101/lm.1845710
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the reconstruction of true and false memories using sensory reactivation and the misinformation paradigms

Abstract: Many current theories of false memories propose that, when we retrieve a memory, we are not reactivating a veridical, fixed representation of a past event, but are rather reactivating incomplete fragments that may be accurate or distorted and may have arisen from other events. By presenting the two phases of the misinformation paradigm in different modalities, we could observe sensory reactivation of the auditory and visual cortex during the retrieval phase. Overall, true and false memories showed similar brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
104
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 32 publications
12
104
3
Order By: Relevance
“…It is one of the processes underlying the misinformation paradigm (Loftus, 2005), where subjects witness some event and then later are given incorrect information about it. Many people are misled into not only believing the new information, but incorporating it into their original memory; when directly asked about the source of the memory, many people specifically claim that they saw it in the original event (e.g., Zhu et al, 2012;Stark, Okado, & Loftus, 2010). While in this case the later new information-the BWC footage-is not inaccurate, it may be misleading or incomplete (e.g., if the camera is shaky or misses important context) or not what they originally perceived, and the same difficulty in accurately remembering the source of new information is likely to apply.…”
Section: Pre-viewing Of Body Camera Footagementioning
confidence: 99%
“…It is one of the processes underlying the misinformation paradigm (Loftus, 2005), where subjects witness some event and then later are given incorrect information about it. Many people are misled into not only believing the new information, but incorporating it into their original memory; when directly asked about the source of the memory, many people specifically claim that they saw it in the original event (e.g., Zhu et al, 2012;Stark, Okado, & Loftus, 2010). While in this case the later new information-the BWC footage-is not inaccurate, it may be misleading or incomplete (e.g., if the camera is shaky or misses important context) or not what they originally perceived, and the same difficulty in accurately remembering the source of new information is likely to apply.…”
Section: Pre-viewing Of Body Camera Footagementioning
confidence: 99%
“…For example, several studies have reported that brain regions involved in encoding or retrieving sensory-perceptual information tend to be more active during retrieval of true than false memories (e.g., [24][25][26][27]29,32 ).…”
Section: Distinguishing True and False Memories With Neuroimagingmentioning
confidence: 99%
“…For example, after seeing pictures of some objects (e.g., a photo of a car) and imagining others in response to a verbal cue (e.g., 'imagine a ball'), participants sometimes falsely remember that they saw a picture of an item that they only imagined (i.e., a ball). Still other neuroimaging studies have examined false memories that result from the presentation of misinformation after viewing an everyday event [30][31][32] . For example, after watching a man steal a woman's wallet, some subjects receive misinformation about what actually happened (e.g., the woman's arm was hurt during the robbery, rather than her neck), which they later remember as part of the original event.…”
Section: Distinguishing True and False Memories With Neuroimagingmentioning
confidence: 99%
“…A question that intrigues many researchers, though, is to what extent this false recognition can be distinguished from true recognition (Schacter & Slotnick, 2004;Stark, Okado, & Loftus, 2010). The question is somewhat complicated by the fact that participants in such studies make recognition errors for multiple reasons.…”
mentioning
confidence: 98%